2016
DOI: 10.1007/s10209-016-0499-3
|View full text |Cite
|
Sign up to set email alerts
|

Why do few assistive technology systems make it to market? The case of the HandyHelper project

Abstract: Assistive technologies, such as telecare monitoring applications installed in the home, are being promoted to help reduce pressure on health care systems caused by an aging population and as such promise a large market for new products. However, despite many projects undertaken by commercial companies, and despite significant investments both by the companies and by national and international funding programs in the EU, such systems are not widespread. This paper reports on a retrospective study of the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In workshop 2, more than half of the issues related to Financing were given the highest rating (7 of 12) and all issues given the highest rating were from this category. Funding problems can result in entire projects being stopped, which was demonstrated by the case studies done previously [20,21]. But they can also lead to people changing the focus.…”
Section: Money Is Always Importantmentioning
confidence: 78%
See 2 more Smart Citations
“…In workshop 2, more than half of the issues related to Financing were given the highest rating (7 of 12) and all issues given the highest rating were from this category. Funding problems can result in entire projects being stopped, which was demonstrated by the case studies done previously [20,21]. But they can also lead to people changing the focus.…”
Section: Money Is Always Importantmentioning
confidence: 78%
“…But they can also lead to people changing the focus. One of the case studies that led to this study being done found that due to costs associated with installation and maintenance a company switched from focusing on people in their own homes to those in care homes; this in turn affected the needs to be addressed in subtle ways and ultimately may have affected the success [21]. Thus, funding agencies may want to reconsider funding guidelines to better support this phase, for example, by providing more flexibility, as suggested by the participants of workshop 1 (see Figure 7), even if this just means delaying the time at which results are submitted with no additional funding, or providing new funding schemes aimed at this.…”
Section: Money Is Always Importantmentioning
confidence: 99%
See 1 more Smart Citation
“…■ a retrospective analysis of a more comprehensive system known in advance to have not been entirely successful (Hallewell Haslwanter and Fitzpatrick, 2016), referred to as Case Study 2; and ■ a study consulting people with experience in these types of development projects that aimed to identify common issues and elicit recommendations (Hallewell Haslwanter and Fitzpatrick, 2017), called the third study.…”
Section: Methodsmentioning
confidence: 99%
“…To deal with these problems a wide range of assisting technologies are developed and tested in research projects. Despite the intensive research efforts only few systems make it to the market [6]. Common pitfalls are again a lack in user acceptance and wrong assumptions about the target group as well as financial and economic issues, which hinder a successful launch.…”
Section: Introductionmentioning
confidence: 99%